2015
DOI: 10.1093/brain/awv100
|View full text |Cite
|
Sign up to set email alerts
|

Parietofrontal motor pathways and their association with motor function after stroke

Abstract: Corticocortical interactions between the primary motor cortex, the ventral premotor cortex and posterior parietal motor areas, such as the anterior and caudal intraparietal sulcus, are relevant for skilled voluntary hand function. It remains unclear to what extent these brain regions and their interactions also contribute to basic motor functions after stroke. We hypothesized that white matter integrity of the underlying parietofrontal motor pathways between these brain regions might relate to residual motor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 54 publications
6
85
0
Order By: Relevance
“…The present data is well in line with a variety of reports showing that a stroke leads to the disruption of the CST a and that its residual structural state critically influences residual motor output (Lindenberg et al, 2010, Rüber et al, 2012, Schaechter et al, 2009, Schulz et al, 2015b), for a comprehensive review please see Koch and colleagues (Koch et al, 2016). It has already been suggested that these remote lesion effects might also lower white matter integrity of aMF a comprising cortico-rubro-spinal and cortico-reticulo-spinal fibers due to Wallerian degeneration (Lindenberg et al, 2012, Schaechter et al, 2009), particularly originating from M1 (Rüber et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present data is well in line with a variety of reports showing that a stroke leads to the disruption of the CST a and that its residual structural state critically influences residual motor output (Lindenberg et al, 2010, Rüber et al, 2012, Schaechter et al, 2009, Schulz et al, 2015b), for a comprehensive review please see Koch and colleagues (Koch et al, 2016). It has already been suggested that these remote lesion effects might also lower white matter integrity of aMF a comprising cortico-rubro-spinal and cortico-reticulo-spinal fibers due to Wallerian degeneration (Lindenberg et al, 2012, Schaechter et al, 2009), particularly originating from M1 (Rüber et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…They were evaluated by means of grip force (calculated as the ratio between the affected and unaffected hand, mean value 0.2 ± 0.3, range 0–1.2) and the upper limb score of the Fugl-Meyer assessment (mean value 40.1 ± 19.3, range 4–66). In order to calculate a more general motor score including distal and proximal motor components, both measures were combined to one composite motor output score (MO) by principal component analysis (1st principal component explaining 75% of variance in both measures) as applied in previous trials (Schulz et al, 2015b). Table 1 summarizes the clinical data for all patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the structural changes, the lesion volume has little explanatory value of motor function after stroke (Puig et al, ; Schiemanck, Kwakkel, Post, Kappelle, & Prevo, ), whereas the lesion location (Crafton, ; Shelton & Reding, ) and the microstructural white matter integrity has been shown to strongly determine motor function (Koch & Hummel, ). In particular, better integrity of the lesioned corticospinal tract (CST) is positivity correlated with better motor function (Lindenberg et al, ; Schulz et al, ; Schulz et al, ). Disconnection from descending pathways results in neuroplastic changes toward alternative motor network activation patterns.…”
Section: Introductionmentioning
confidence: 99%